Determinant analysis of land and building taxpayers' compliance and happiness in East Lombok Regency - Yuli Astini; Made Kembar Sri Budhi; I Made Suyana Utama; I Wayan Ramantha (Contemporary Economics, 2024)
Local taxes are one of the local government's resource revenue in creating happiness. This study aims to ana- lyze the influence of Good Governance Implementation, Tax Literacy, Demographic Factors, and Motivation on Land and Building Taxpayers' Compliance and Happiness in East Lombok Regency and analyze the role of Taxpayer Compliance in the mediation of Good Governance Implementation, Tax Literacy, Demographic Factors, and Motivation towards the Taxpayers Happiness of L&B in East Lombok Regency. The population in this study was 26,965 taxpayers, and 177 respondents were selected as the sample using stratified sampling techniques. The data were collected from non-participant observation and in-depth structured interviews and were analyzed using SEM-PLS. The results showed that: (a) The implementation of good governance, tax literacy, demographic factors and taxpayer motivation was able to improve L&B taxpayer compliance in East Lombok Regency; (b) Taxpayer motivation and taxpayer compliance could increase taxpayer happiness opti- mally, but the implementation of good governance, tax literacy and demographic factors could not increase the L&B taxpayers happiness in East Lombok Regency; and (c) Indirect implementation of good governance, tax literacy, demographic factors and taxpayer activity could increase taxpayer happiness through L&B tax- payer compliance in East Lombok Regency.
Keywords: H26; I31; 330; implementation of good governance; demographic factors; taxpayer motivation; taxpayer compliance; taxpayer happiness